HUBUNGAN KUANTITATIF STRUKTUR-AKTIVITAS (HKSA) SENYAWA TURUNAN 1H-BENZO[D]IMIDAZOL DARI ASAM DEHIDROABIETAT SEBAGAI INHIBITOR POLIMERISASI TUBULIN - Nujaimah
Cancer is a disease that caused by uncontrolled division of abnormal cells. There are several types of cancer, one of them is liver cancer which is on the fourth place of the most common causes of death in 2018. There are many kinds of cancer drug, antimicrotubule is one of them. Antimicrotubule agents interfere mircrotubules causing the cells unable to multiply. 1Hbenzo[d]imidazole derivates of dehydroabietic acid serves as antimicrotubules. The aim of the present study is to design new 1H-benzo[d]imidazole derivates of dehydroabietic acid that have better activity than the one that has existed. The method used in this study is Quantitative Structure-Activity Relationship (QSAR) with Hansch analysis. The training set used in this study is 22 1H-benzo[d]imidazole derivates of dehydroabietic acid that have been tested in vitro to liver cancer cell HepG2. The best QSAR equation obtained is LogIC50 = ?17.820 ± (3.744) + (2.462 ± 0.320) × AM1_LUMO + (18.290 ± 3.474) × density –(2.642 ± 0.429) × logP + (11.152 ± 1.686) × mr –(0.278 ± 0.042) × vol. Using the best QSAR equation, 24 new derivatives were designed and 10 of them were found to have lower predicted IC50 values than the parent compound, compound 7e. The compounds were docked to tubulin, and seven derivatives were found to have lower binding energy than that of the parent compound. Compound T1 has lower IC50 predicted value than that of parent compound and is predicted to has better interaction with tubulin.